Fitness consequences of dietary patterns and consumption in young girls - Ahmed , Sadaf; Noushad , Shamoon; Nadeem, Mahnoor (International Journal of Endorsing Health Science Research, 2015)
The investigation of usual dietary patterns are of physiological significance including carbohydrate rich diet, caffeine consumption, protein intake specifically red and white meat along with intake of dietary supplements, milk and juices utilization as they have known to effect BMI and body fat distribution of those with increasing body weight, underweight and normal weight. The study was carried out on 435 university girls aged between 18 to 25 Years, we used the multiple logistic to investigate the relationship of dietary habits, family history, BMI, waist-hip ratio and body fat distribution. The result showed that there is no direct relation of body mass with dietary habits as the Girls with BMI <18 found to take the diet characterized by decrease consumption of good diet (milk, juices, egg, mineral supplements) and increase consumption of bad diet (junk food, fried and oil rich food), while girls with > 23 considered as overweight found diet conscious and were taking healthy diet. The association of these dietary patterns with raised body fat distribution, BMI and hip to waist ratio may specify the risk of developing health maladies but we conclude that in our population the lean girls are taking more junk food and are prone to various diseases more than the obese. We recommend that these unhealthy dietary patterns should be avoided as they may be a silent cause of many health issues.